Analysis of Exchange Rate Pass-Through in Indonesia With VECM Approach - Malisa, Nor; Karsinah, Karsinah (Universitas Negeri Semarang, 2019)
The purpose of this research is to determine and analyze the degree of pass-through in Indonesia, which calculated from the cumulative response of the exchange rate to the CPI and the exchange rate on the exchange rate it self. Data used in this research is quarterly from 1997Q3 to 2017Q4. The variables used in this research are consumer price, rupiah to dollar exchange rate, producer price index, import price index, SBI interest rates, US wholesale price index. Data has sourced by Bank Of Indonesia and International Monetary Fund. The method used in this research is Vector Error Correction Model (VECM). The results showed that in the long-term exchange rate, producer price index, import price index, US wholesale price index had a positive effect on CPI while SBI interest rates had a negative effect to the consumer price. The impulse response function test states that in the first quarter only the variable itself was responded by the CPI, the second quarter import price index at the most by 1.2% was able to respond to the CPI. The results of the pass-through degree in Indonesia show that producer price is 0.009 and consumer price is -0.002. The result of variance decomposition shows that the import price index has the largest contribution in influencing the consumer price index. Have to reduce imports of raw materials for self-consumption, but have to import for re-export, so that domestic prices in Indonesia are stable. Tujuan penelitian ini untuk mengetahui dan menganalisis derajat pass-through di Indonesia yang dihitung dari kumulasi respon kurs terhadap IHK dan kurs terhadap kurs. Data yang digunakan dalam penelitian ini adalah data time series triwulan dari tahun 1997Q3 hingga 2017Q4.Variabel yang digunakan dalam penelitian ini antara lain indeks harga konsumen, nilai tukar rupiah per dolar, indeks harga produsen, indeks harga impor, suku bunga SBI, indeks harga perdagangan besar AS. Metode yang digunakan adalah Vector Error Correction model (VECM). Hasil penelitian menunjukkan bahwa pada jangka panjang variabel nilai tukar,indeks harga produsen, indeks harga impor, indeks harga perdagangan besar AS berpengaruh positif terhadap IHK sedangkan suku bunga SBI berpengaruh negatif terhadap IHK. Hasil uji impulse response function menyatakan bahwa pada kuartal pertama hanya variabel itu sendiri yang direspon oleh IHK, kuartal kedua indeks harga impor paling besar sebesar 1.2% mampu direspon IHK. Hasil derajat pass-through indeks harga produsen sebesar 0.009 dan indeks harga konsumen sebesar -0.002. Hasil variance decomposition menunjukkan bahwa indeks harga impor mempunyai kontribusi terbesar dalam mempengaruhi indeks harga konsumen. Perlu mengurangi impor bahan baku untuk konsumsi sendiri, namun mengimpor untuk diekspor kembali supaya tingkat harga domestik di Indonesia stabil.